Correlation between motor abilities of handball referees and quality of refereeing - Belcic, I.; Ruzuc, L.; Marosevic, A. (World Congress of Performance Analysis of Sport XII, 2018)
The aim of this study was to determine correlation of motor abilities and quality of refereeing in Croatian national and international handball referees. Examinees were 32 handball referees from Premier Croatian Handball League. They are divided in pairs in which they are refereeing a match during their career. The list of Premier league handball referees is made every year according to previous performance by the professional committee of the Croatian Handball Referees Association. Testing of handball referees was performed in two parts: the first part of the testing was performed at the Diagnostic Center of the Faculty of Kinesiology of the University of Zagreb. All examinees had protocol of warm up which lasted for 20 minutes and after warm up examinees conducted motor abilities testing in 5 different motor tests which measure agility, coordination and explosive sprint power. The second part of testing was performed on official Premier Croatian Handball League matches. With multiple regression test variables were tested to check if there is correlation of motor abilities (independent variables) and quality of refereeing (dependent variable) and the level of significance was set at p < 0.05. In frontal agility test with 180 degrees turn a statistically significant negative correlation was obtained with quality of refereeing. Negative correlation explains that a lower result in the test (reverse scaled variable - lower value is a better result) means better quality of refereeing. In the motor test eights with bending, the results of multiple regression analysis show a statistically significant positive correlation with the quality of the refereeing. The scientific contribution of this research is reflected in the correlation of motor abilities and quality of refereeing, and in particular refers to frontal agility test with 180 degrees turn. Movement in the test also reflects the movements of referees during the handball match and it is recommendablethat this test should be used in official handball referees tests during official seminars.